2013
DOI: 10.1117/12.2007351
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-wave operation of green/yellow laser diodes based on BeZnCdSe quantum wells

Abstract: We have demonstrated continuous wave operation of BeZnCdSe quantum well laser diodes at room temperature in the green to yellow spectrum range. The laser diodes structures were grown by molecular beam epitaxy. To overcome low doping ability of a p-cladding layer materials of BeMgZnSe, a short-period superlattice of BeMgZnSe/ZnSe:N was employed. High-power lasing over 50mW at a peak wavelength of 536 nm was achieved. By employing highly strained BeZnCdSe quantum wells, continuous wave lasing up to 570 nm has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the ZnSe/BeTe GSL, BeTe thickness increases with a fixed grading step, while ZnSe thickness decreases with the same fixed step, when next period of ZnSe/BeTe is grown, so that one period thickness is kept constant as shown in figure 1(right), where one period thickness as well as fixed step thickness is a parameter for optimization. Previously, it was found that GSL layer with one period thickness of 13 ML with 1 ML step gives the lowest voltage at 200A/cm 2 current injection [16]. In this report, a fixed step is further reduced to 0.5 ML to get a smoother grading potential profile in a GSL.…”
Section: Znse/bete P-grading Superlatticementioning
confidence: 87%
“…In the ZnSe/BeTe GSL, BeTe thickness increases with a fixed grading step, while ZnSe thickness decreases with the same fixed step, when next period of ZnSe/BeTe is grown, so that one period thickness is kept constant as shown in figure 1(right), where one period thickness as well as fixed step thickness is a parameter for optimization. Previously, it was found that GSL layer with one period thickness of 13 ML with 1 ML step gives the lowest voltage at 200A/cm 2 current injection [16]. In this report, a fixed step is further reduced to 0.5 ML to get a smoother grading potential profile in a GSL.…”
Section: Znse/bete P-grading Superlatticementioning
confidence: 87%